LEVEL OF BLOOD PRESSURE CONTROL AMONG HYPERTENSIVE PATIENTS RECEIVING TREATMENT AT FEDERAL MEDICAL CENTRE NGURU YOBE STATE NORTH EASTERN NIGERIA - Musa MB; Talle AM; Buba F; Gezawa ID; Abdul H (Ntec Specialist, 2018)
Background: Hypertension remains the most readily identifiable and reversible risk factor for cardiovascular diseases (CVD) and is the leading cause of death worldwide. Despite the avalanche of medications for the management of elevated blood pressure, adequate control of systemic hypertension has largely remained enigmatic. Previous studies from African countries including Nigeria have shown that blood pressure (BP) control still remained poor. The objective of this study therefore was to determine the level of blood pressure control among hypertensive patients on treatment and identify associated factors. Methodology: The study was an observational, cross-sectional study of consecutive hypertensive patients attending the general outpatient, cardiac, endocrine and renal clinics at the Federal Medical Centre Nguru, in northeastern Nigeria; conducted over a period of six months from June 2016 to December 2016. Result: A total of two hundred and ninety one (291) consecutive subjects, comprising 134(46.1%) males and 157(53.9%) females were recruited. The mean age of the study population was 56.15±12.72.There was no difference in the mean age of subjects with controlled and uncontrolled hypertension 57.13±12.97 and 55.48±12.54 respectively with P = 0.275. One hundred and nineteen (40.9%) subjects had controlled hypertension while the remaining 172(59.1%) had uncontrolled hypertension. There was a significant difference in the mean systolic and diastolic blood pressure of subjects with controlled and uncontrolled hypertension (116.22± 12.14 and 153.14±18.17) P = 0.001 and (73.78±8.02 and 89.53±11.12) P = 0.001 respectively. The predominant pattern of uncontrolled hypertension among the study population was combined systolic and diastolic hypertension. Conclusion: Our study revealed that blood pressure control among hypertensives on medication was not optimal, decreased glomerular filtration rate, low anti-hypertensive medication adherence and use of NSAID were found to be responsible for the inadequate blood pressure control observed in this study. Poverty and ignorance were major contributing factors for low medication adherence.